Paediatric partial‐thickness scald burns – is Biobrane the best treatment available? - Mandal, Anirban (Int Wound J, 2007)
The article critically analyses the role of Biobrane, one of the widely used modern biosynthetic dressings, in paediatric partial‐thickness scald burns. Most of the studies, available in the literature, confirmed that Biobrane has significantly reduced the hospital stay, wound healing time and requirements of pain medications. However, very few studies with long‐term follow up are available. Further randomised controlled trials are required to challenge the supremacy of Biobrane in paediatric partial‐thickness burns.